Clinical features of myasthenia gravis with neurological and systemic autoimmune diseases - Zhu, Ying; Wang, Benqiao; Hao, Yuehan; Zhu, Ruixia (Frontiers in Immunology, 2023)
Multiple reports on the co-existence of autoimmune diseases and myasthenia gravis (MG) have raised considerable concern. Therefore, we reviewed autoimmune diseases in MG to explore their clinical presentations and determine whether the presence of autoimmune diseases affects the disease severity and treatment strategies for MG. We reviewed all the major immune-mediated coexisting autoimmune conditions associated with MG. PubMed, Embase and Web of Science were searched for relevant studies from their inception to January 2023. There is a higher frequency of concomitant autoimmune diseases in patients with MG than in the general population with a marked risk in women. Although Most autoimmune comorbidities are linked to AChR-MG; however, there are few reports of MuSK-MG. Thyroid disorders, systemic lupus erythematosus, and vitiligo are the most common system autoimmune diseases associated with MG. In addition, Importantly, we first reviewed that MG can coexist with neurological autoimmune diseases, such as neuromyelitis optica (NMO), inflammatory myopathy (IM), multiple sclerosis (MS), and autoimmune encephalitis (AE), with NMO being the most common. Furthermore, Autoimmune diseases appear to develop more often in early-onset MG (EOMG). Moreover, MS are prone to coexists more commonly with EOMG, while IM are apt to coexists with LOMG. In addition, MG complicated by with autoimmune diseases tends to have mild clinical manifestations, and the coexistence of autoimmune diseases does not influence the clinical course of MG. In contrast, The clinical course of neurological autoimmune diseases is typically severe. Autoimmune diseases occur most often after MG or as a combined abnormality; therefore, timely thymectomy followed by immunotherapy could be effective. In addition, thymoma-associated AChR MG is associated with an increased risk of AE and IM, whereas NMO and MS are associated with thymic hyperplasia. The co-occurrence of MG and autoimmune diseases could be attributed to similar immunological mechanisms with different targets and common genetic factor predisposition. This review provides evidence of the association between MG and several comorbid autoimmune diseases.